2011
DOI: 10.1007/s10529-011-0713-6
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives of the Escherichia coli RNA degradosome

Abstract: Many biological processes in the cell are linked to RNA metabolism and therefore have implications for a wide range of biotechnological applications. The processing and degradation of RNA plays an important role in RNA metabolism with often the same enzymes being involved in both processes. In this review, we highlight the dynamic nature of the structural components of the Escherichia coli RNA degradosome which is a large multiprotein complex that plays an important role in RNA degradation. The activities of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 116 publications
0
7
0
Order By: Relevance
“…The brisk removal of S1 in our system provided a unique opportunity to detect any immediate changes in the abundance of mRNAs, with the intent of identifying direct influences of S1. We placed focus on several mRNAs: that which encodes S1 itself (rpsA), those encoding proteins that physically interact with S1 (S2 [rpsB], RNase E [rne], PNPase [pnp]) (1,10,17,37,38), messages known to be degraded by the degradosome and stabilized by S1 (CspE and S15 [rpsO]) (9,16,40), a collection of unrelated mRNAs with diverse 5= untranslated regions (UTRs) and translation initiation features (encoding LacI, LacZ, OmpT, and RecA), and two housekeeping transcripts (encoding GAPDH [gapA] [11,43,49,51] and CsdA [36,44]). …”
Section: Resultsmentioning
confidence: 99%
“…The brisk removal of S1 in our system provided a unique opportunity to detect any immediate changes in the abundance of mRNAs, with the intent of identifying direct influences of S1. We placed focus on several mRNAs: that which encodes S1 itself (rpsA), those encoding proteins that physically interact with S1 (S2 [rpsB], RNase E [rne], PNPase [pnp]) (1,10,17,37,38), messages known to be degraded by the degradosome and stabilized by S1 (CspE and S15 [rpsO]) (9,16,40), a collection of unrelated mRNAs with diverse 5= untranslated regions (UTRs) and translation initiation features (encoding LacI, LacZ, OmpT, and RecA), and two housekeeping transcripts (encoding GAPDH [gapA] [11,43,49,51] and CsdA [36,44]). …”
Section: Resultsmentioning
confidence: 99%
“…This assumption is also supported by previous studies, which showed that degradation of certain bacterial RNAs might involve endonucleolytic cleavages by RNase E at a single-stranded AU-rich region in the 3′UTR 30 33 34 . In E. coli , the degradation of many mRNAs is initiated by an endonucleolytic cleavage catalyzed by RNase E, which products serve as the substrates for additional RNase E cleavages as well as for digestion by the 3′→5′exonucleases, polynucleotide phosphorylase (PNPase) and RNase II 35 36 37 38 . Figure S4 indicates that the low mRNA stability seemed to result in reduction of the bmoF1 mRNA level in E. coli BL21(DE3), which in turn decreased total expression level of bmoF1 .…”
Section: Discussionmentioning
confidence: 99%
“…In response to cold stress, RhlB can be exchanged with DeaD (in vitro and in vivo) or RhlE (in vitro) to produce a cold stress degradosome 93 , 94 . Stoichiometry of subunits is not known, however a model in which PNPase:RNase E:enolase:RhlB associate in a ratio of 4:3:8:8 binding to the C-terminus of RNase E has been proposed 131 . Similar to E. coli , the B. subtilis and Staphylococcus aureus degradosomes assemble on RNase Y (RNase E equivalent) 105 and are composed of the RNA helicase CshA (RhlB equivalent), enolase and PnpA (PNPase equivalent).…”
Section: Rna Helicases In Rna Turnovermentioning
confidence: 99%